Training needs in TQM: the Portuguese perspective - Leal, Rogério P. (2008)
A survey to assess training needs in TQM was developed in several European countries, within the framework of a Leonardo’s project named IMVOCED. Beyond a comparison of the results in each country, a global analysis was performed to design a TQM programme to be delivered by WBL (Work Based Learning). Differences were found between countries, and the Portuguese results also revealed that different approaches to TQM training should be adopted according to the organisation’s dimension. Based on this evidence, two different strategies for TQM training by WBL are proposed and discussed.